(untitled) (Palimpsesto, 2018)
In this article, we will make an approach to the reception of Albert Camus thought and figure in theChilean cultural field during the first postwar years. Its reception was an important phenomenon for thearticulation and consolidation of several cultural projects that focus their attention in Frenchexistentialism, intellectual atmosphere from which we can’t separate the circulation of Camus’ works inthe region. In this sense, we have chosen to work following what it’s known in intellectual history as “theproblem of reception”, considering as primary sources the cultural magazines of the time, the mostimportant devices in which the existentialist reception materialized in this first postwar years.